(untitled) (Research, Society and Development, 2020)
This article is an integrative review. To inspect, through the databases, articles with the theme “childbirth education in Primary Health Care”. In addition, it aims to analyze, from a Freirian perspective, the health education offered in prenatal care to pregnant women and their support network. The databases were as follow: Scielo, Pubmed and BVS (Biblioteca Virtual de Saúde) to select the articles; through the descriptors: Health Education, Nurses, Primary Health Care and Prenatal Education. We obtain a total of 6 articles that fit the selection requirements. The need to prepare pregnant women in Primary Health Care is observed, involving her support network for educational activities for the moment of birth, as also clarifying her doubts and establishing the bonding relationship with the professional who helps her. There is a reflection on the strengthening of the educative role exercised by nurses in their actions, bringing them closer to issues related to childbirth and the importance of their intervention in the construction of empowered pregnant women, also protagonists of childbirth.